Legal aid for poor persons - Molony, Thomas F., Sir (Statistical and Social Inquiry Society of Ireland, 1931)
At the annual meeting of the English Bar held on the 11th February, 1928, a discussion arose on the question of legal aid to poor persons, and the Attorney-General, Sir Douglas Hogg (now Lord Hailsham) said, in winding up the debate :? " The generosity of the medical profession was a byword and an example to the rest of the world, and the lawyers, although they lagged behind, did more perhaps than was generally recognised to assure that the poor of this country had that expert help which they could not otherwise afford. I should like to see the day coming when just as medicine administers to all who need it help for the body, so in every great centre of population we might see something akin to a legal hospital where the poor people could rely on getting the advice and help which they needed.'
Read before the Society on Wednesday, February 4th, 1931
Keywords: Legal aid; Charity; 314.15